(untitled) (Islas, 2021)
The productive process of the news becomes a set of operations carried out by the media to process a raw material, the current affairs, which they turn into a periodically elaborated product, the news. This article focuses its attention on the preparation of the news and the elements that intervene in the elaboration of the communicative product, focusing on two of them: the journalistic language and the sources of information, in order to offer an explanation to the presence of the bureaucratic or administrative language in the Cuban press today.